Water pollution, cholera, and the role of probiotics: a comprehensive review in relation to public health in Bangladesh - Chowdhury, Md. Rayhan; Islam, Ariful; Yurina, Valentina; Shimosato, Takeshi (Frontiers in Microbiology, 2025)
Cholera, a disease caused by Vibrio cholerae, remains a pervasive public health threat, particularly in regions with inadequate water sanitation and hygiene infrastructure, such as Bangladesh. This review explores the complex interplay between water pollution and cholera transmission in Bangladesh, highlighting how contaminated water bodies serve as reservoirs for V. cholerae. A key focus is the potential role of probiotics as a novel intervention approach for cholera prevention and management. Probiotics are promising as an adjunctive approach to existing therapies as they can enhance gut barrier function, induce competitive exclusion of pathogens, and modulate host immune responses. Recent probiotic advancements include engineering strains that disrupt V. cholerae biofilms and inhibit their virulence. Integrating probiotics with traditional cholera control measures could significantly enhance their effectiveness and provide a multifaceted approach to combating this persistent disease. This review aims to shed light on the potential of probiotics in revolutionizing cholera management and to offer insights into their application as both preventive and therapeutic tools in the fight against this enduring public health challenge.